In vivo CRISPR screens reveal potent driver mutations in head and neck cancers. (3rd July 2020) - Loganathan, Sampath Kumar; Schramek, Daniel
ABSTRACT: We have recently tested the transforming potential of 484 'long-tail' genes, which are recurrently albeit infrequently mutated in head and neck cancers (HNSCC). We identified 15 novel tumor suppressors and our top hits converge on regulating the NOTCH signaling pathway. Therapeutic approaches activating NOTCH signaling could be a promising strategy to treat two-thirds of human HNSCC patients.